Examination of Uncertainties in the Corrosion-Fatigue Design and Assessment of Offshore Wind Support Structures - DeFrancisci, John (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Civil Engineering.; Advisor: Dan Kuchma.; Committee: Eric Hines, Geoffrey Swain, Colin Orians, and Samantha Jo-Fried.; Keywords: Civil engineering, Energy, and Environmental engineering.